Respuesta :

For this case we have the following function:
 f (x) = ((x + 2) ^ 2) * (x-4) * (x + 1) ^ 3
 The roots are given by:
 ((x + 2) ^ 2) * (x-4) * (x + 1) ^ 3 = 0
 x + 2 = 0
 x = -2 (multiplicity 2)
 x-4 = 0
 x = 4 (multiplicity 1)
 x + 1 = 0
 x = -1 (multiplicity 3)
 Answer:
 
option A
S1NGH

Answer:

Following function:

 f (x) = {(x + 2)²} × (x-4) × (x + 1)³

 The roots are given by:

 {(x + 2)²} × (x-4) × (x + 1)³ = 0

 x + 2 = 0

 x = -2

 x-4 = 0

 x = 4

 x + 1 = 0

 x = -1

 Answer:

 option A

Step-by-step explanation: